Occurrence of multidrug-resistant Acinetobacter baumannii and Escherichia coli in veterinary healthcare facilities in Klang Valley, Malaysia - Ng, S. Y.; Abdul Aziz, Saleha; Bejo, Siti Khairani; Dhaliwal, Gurmeet Kaur (Veterinary Association Malaysia, 2016)
Multidrug-resistant organisms (MDROs) such as multidrug-resistant (MDR) Acinetobacter baumannii and Escherichia coli are important pathogens associated with nosocomial infections in both human and animal health care facilities. Surfaces of inanimate objects in health care facilities can serve as sources of infection. However, studies on prevalence of these pathogens in veterinary settings are lacking in the country. Therefore, the objectives of this study were to determine the occurrence of A. baumannii and E. coli and the occurrence of MDR isolates on surfaces of inanimate objects in veterinary health care facilities in Klang Valley, Malaysia. In this study, swab samples were taken from 65 surfaces of inanimate objects that included door knobs, examination tables, labcoats, stethoscopes and weighing scales. The swab samples were cultured and all isolates were subjected to antibiotic susceptibility test. The study revealed that the occurrence of A. baumannii was 9.23% and 5 out of 6 (83.33%) A. baumannii isolates were classified as MDR. However, no E. coli was isolated. In conclusion, surfaces of inanimate objects can be a source of MDR A. baumannii in veterinary health care facilities that is of animal and public health concern.